ISOLATION AND CHARACTERIZATION OF A TRITERPENOID FROM GENTIANELLA THYRSOIDEA FABRIS HOOKER - Tomás Ch., Gloria (2001)
On the investigation of Gentiane/la thyrsoidea Hooker Fabris (root, stem, flowers) was isolated a triterpenoid: oleanolic acid. Structure was elucidated by spectroscopic methods (IR, NMR-'3C y DEPT).